638. The Impact of in vitro Synergy Between Colistin and Meropenem on Clinical Outcomes in Invasive Carbapenem-resistant Gram-negative Infections: A Report from the OVERCOME Trial. (4th December 2021) - Pogue, Jason M; Rybak, Michael J; Stamper, Kyle; Marchaim, Dror; Thamlikitkul, Visanu; Carmeli, Yehuda; Chiu, Cheng; Daikos, Georgios L; Dhar, Sorabh; Mangoni, Emanuele Durante; Gikas, Achilleas; Kotanidou, Anastasia; et al.
Abstract: Background: Consensus guidelines caution against colistin (COL) monotherapy due to efficacy and resistance development concerns. The COL + meropenem (MEM) combination often displays in vitro synergy against carbapenem-resistant (CR) Gram-negative bacilli (GNB). We recently completed a clinical trial comparing outcomes in patients receiving COL vs. COL + MEM. Herein we assess if, amongst patients receiving COL + MEM, outcomes differed as a function of the presence (or absence) of in vitro synergy against the index pathogen. Methods: OVERCOME was an international, multicenter, randomized, double-blind, placebo-controlled study comparing COL + placebo and COL + MEM for the treatment of pneumonia and/or bloodstream infection (BSI) due to CR GNB. Baseline isolates were COL susceptible (MIC ≤ 2 mg/L) and underwent synergy testing to COL + MEM in 24-hour time kill experiments (TKE). Synergy was defined as a >2-log CFU/ml reduction with combination therapy compared to the most active single agent. Outcomes assessed included 28-day mortality, clinical failure, and the development of COL resistance (MIC ≥ 4 mg/L) for both the overall cohort and the subgroup with A. baumannii . Results: Of the 211 patients who received COL + MEM in OVERCOME, 186 had baseline synergy testing performed and were eligible for this analysis. The median age of the cohort was 70 years, 35% were female, 48% were white, and 44% Asian. Sixty-eight percent were in the intensive care unit (ICU) at infection onset. A. baumannii was the most common pathogen (78%) and pneumonia was the most common infection (68%). Synergy was demonstrated in most isolates (76%). Baseline characteristics, clinical, and microbiological outcomes were similar amongst patients infected with isolates against which COL + MEM demonstrated synergy and those where no synergy was demonstrated (Table 1). In patients with A. baumannii infections, the presence of in vitro synergy was associated with a decrease in clinical failure (53% vs. 79%; p = 0.04). No significant impact of synergy on 28-day mortality or development of COL resistance was demonstrated (Table 2). Conclusion: The presence of in vitro synergy via TKE was associated with a decrease in clinical failure in patients treated with COL + MEM for invasive infections due to CR A. baumannii . Disclosures: Jason M Pogue, PharmD, BCPS, BCIDP, Merck (Consultant)QPex (Consultant)Shionogi (Consultant)Utility Therapeutics (Consultant)VenatoRX (Consultant) Michael J. Rybak, PharmD, MPH, PhD, Paratek Pharmaceuticals (Research Grant or Support) Emmanuel Roilides, MD, PhD, FIDSA, FAAM, FESCMID, Merck Sharp & Dohme Corp. (Consultant, Grant/Research Support) Matthew Sims, MD, PhD, Astra Zeneca (Independent Contractor)Diasorin Molecular (Independent Contractor)Epigenomics Inc (Independent Contractor)Finch (Independent Contractor)Genentech (Independent Contractor)Janssen Pharmaceuticals NV (Independent Contractor)Kinevant Sciences gmBH (Independent Contractor)Leonard-Meron Biosciences (Independent Contractor)Merck and Co (Independent Contractor)OpGen (Independent Contractor)Prenosis (Independent Contractor)Regeneron Pharmaceuticals Inc (Independent Contractor)Seres Therapeutics Inc (Independent Contractor)Shire (Independent Contractor)Summit Therapeutics (Independent Contractor)